Correlation study between anatomopathological data and levels of blood morphine concentrations in heroin-related deaths. (July 2021) - Scendoni, Roberto; Mirtella, Dora; Froldi, Rino; Valsecchi, Marco; Ferrante, Luigi; Cingolani, Mariano
Highlights: In heroin-related death pre-existing pathological processes play a key role. A histopathological score linked to the degree of multi-organ failure prior to death is applied. A relationship between total blood morphine value and pathological score is investigated. Abstract: Heroin-related mortality is a complex phenomenon involving several factors that make an individual more susceptible to opioid toxicity. Among these, pre-existing pathological conditions play an important role. The current paper reviewed 51 autopsied cases performed over the last 30 years, each subject ("frequent heroin user") having taken heroin intravenously alone before death. For each case, total blood morphine concentration determined by gas chromatography–mass spectrometry (GC–MS) was obtained from the archives. For histopathological evaluation we examined microscopic sections of the heart, lung, brain, liver and kidney, and for each organ a score table with a numerical value from 1 to 5, as an indicator of increasing severity, was drawn up. Finally, we created a scoring system based on the Injury Severity Score (ISS), generated by the sum of the squares of the three highest organ scores. We investigated the relationship between total blood morphine value (mg/l) and pathological score by inserting the two variables in a linear regression model: Score = a + b·Morphinemia (p-value <0.001). The results demonstrated a statistically significant correlation between the two variables: individuals with low total blood morphine values tended to have a higher pathological score. Our study provides useful assessment tools for forensic practice, confirming the need to combine two important disciplines in drug death investigation: forensic pathology and toxicology.